1994
DOI: 10.1111/j.1151-2916.1994.tb04654.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Grain Boundaries in Superplastically Deformed Y‐TZP Ceramics

Abstract: The effects of compressive deformation on the grain boundary characteristics of fine-grained Y-TZP have been investigated using surface spectroscopy, impedance analysis, and transmission electron microscopy. After sintering at low temperature (11SO"C), the grain boundaries are covered by an ultrathin (1 nm) yttrium-rich amorphous film. After deformation at 1200"-1300°C under low stress, some grain boundaries are no longer covered by the amorphous film. Yttrium segregation seems to occur only at wetted grain bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The poorer results obtained on the grain boundary conductivity for samples sintered at temperatures below 1198 K cannot be related uniquely with the difference in the grain sizes, since samples LM1173 and LM1198 present important differences in the values of conductivity, while they show grain sizes quite close, 10 and 12 Am, respectively. The macroscopic grain boundary conductivity changes with the grain size [30], but stronger effects are related to the segregation of impurities, imperfect alignment between grains or even formation of a liquid phase [30,31]. In the samples prepared in the present work, the difference in the values of grain boundary resistances seems to be caused by a better connectivity between grains achieved by sintering at higher temperatures.…”
Section: Electrical Characterizationmentioning
confidence: 59%
“…The poorer results obtained on the grain boundary conductivity for samples sintered at temperatures below 1198 K cannot be related uniquely with the difference in the grain sizes, since samples LM1173 and LM1198 present important differences in the values of conductivity, while they show grain sizes quite close, 10 and 12 Am, respectively. The macroscopic grain boundary conductivity changes with the grain size [30], but stronger effects are related to the segregation of impurities, imperfect alignment between grains or even formation of a liquid phase [30,31]. In the samples prepared in the present work, the difference in the values of grain boundary resistances seems to be caused by a better connectivity between grains achieved by sintering at higher temperatures.…”
Section: Electrical Characterizationmentioning
confidence: 59%
“…14 The origin of this segregation is the relaxation of the elastic energy around yttrium atom as a consequence of the difference between the ionic radius of Y 3+ and the Zr 4+ , being around 20% bigger the Y 3+ than Zr 4+ one and has been proved experimentally by means of different techniques. [14][15][16][17][18][19][20] The yttrium segregation depends on the temperature and bulk concentration 19 and also on the grain size. 15 Segregation of the cations to the grain boundaries changes the chemical composition as well as the electric space charge at the boundaries, consequently affecting the deformation processes in which grain boundary mobility is involved, such as grain boundary sliding.…”
Section: Yttrium Segregation At Grain Boundariesmentioning
confidence: 98%
“…A thorough experimental analysis of the yttrium segregation at the grain boundaries is made by Boutz et al. 14 The origin of this segregation is the relaxation of the elastic energy around yttrium atom as a consequence of the difference between the ionic radius of Y 3+ and the Zr 4+ , being around 20% bigger the Y 3+ than Zr 4+ one and has been proved experimentally by means of different techniques. [14][15][16][17][18][19][20] The yttrium segregation depends on the temperature and bulk concentration 19 and also on the grain size.…”
Section: Yttrium Segregation At Grain Boundariesmentioning
confidence: 99%
“…[7][8][9][10][11][12] Hence, a grain-growth mechanism in Y-TZP was interpreted theoretically by taking into account the presence of this amorphous phase. However, Ikuhara et al 13 conducted detailed HREM observations and nanoprobe EDS measurements in Y-TZP, and concluded that no amorphous phase exists along the grain boundaries and Y 3ࢪ ions segregate along the grain boundaries over a width of 4-6 nm.…”
Section: Introductionmentioning
confidence: 99%